OPEC investment strategies—Past and future - Hamid Bagh-Shomali (Intereconomics, 1983)
Some forecasters recently have predicted that OPEC countries with continuing current account surpluses will shift from long-term to short-term investments in the near future to improve their liquidity positions. However, careful study of a variety of data, including historical patterns, suggests that this will not be the case. Instead, surplus countries will turn even more to long-term investments offering higher returns over time.
Keywords: 330; Oil Funds